The Effect of Two Instructional Performance Methods Hand Stand and Cartwheel in Artistic Gymnastics for Women - Safaa, Yusra (Journal of Physical Education, 2016)
The researcher notes from her experience in this field of teaching to implement these two methods under study in order to see which is best suited or good, if you will speed up the process of teaching the students in these two skills (handstand and Cartwheel) which they are two basic skills in ground movements, and in view of their importance, these two movements approach has been combining to achieve a scientific fact may be useful to specialists, researchers and students alike, and the aim of the research to identify the effect of these two methods and the difference between the effect of two groups cooperative and alternative learning methods in learning handstand and cartwheel with junior high students in Al-forat High School. and she imposed that there are significant statistically differences between the two tests (pre- posttest) to learn two skills handstand cartwheel and with collaborative and interactive methods with junior high students in Al-forat High School, and statistically significant differences between the results of two tests (pre- posttest) for both groups (collaborative and alternative) in learning the female students in junior student in the fifth stage at Al-forat high school, the researcher used the experimental method with two experimental groups because it is suitability for the nature of the research, was used statistical package (SPSS): the arithmetic mean, standard deviation, (T. test) of the dependent and independent samples, and concluded that both methods have an effect on the development of hand stand and cartwheel skills, and recommended to use both collaborative and interactive methods in learning these two skills hand stand and cartwheel in gymnastic because they are influential and successful methods.